Fluororubber sealing ring based on sealing contact pin and preparation process of fluororubber sealing ring
By adopting modified white carbon black and composite filler, the problem of high combustionability and insufficient anti -aging ability under high temperature conditions under high temperature conditions is solved, and higher safety and aging resistance is achieved.
Patent Information
- Application Number
- CN202411667012.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-24
AI Technical Summary
The existing fluoroelastic sealing rings have high combustibility under high temperature conditions, and flame retardants may affect their physical properties and processing characteristics, resulting in a decrease in anti-aging ability.
Using modified silica and composite fillers, the boric acid ester bond is generated through the reaction of 4-vinylbenzene boric acid and tea polyphenols, which is combined with the P-H bond of DOPO to react to generate a flame retardant, and is modified through the EDC/HOBt dehydration system. Carbon fibers are grafted onto carboxylated carbon nanotubes to prepare modified silica and composite fillers with flame retardant and antioxidant effects.
It significantly reduces the combustion of fluorine rubber at high temperature conditions, improves its safety and application reliability, and significantly improves the aging resistance of fluorine rubber sealing rings, and improves the performance stability and sealing effect of long -term use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluororubber, in particular to a fluororubber sealing ring based on a sealing pin and a preparation process thereof. Background Art
[0002] With the development of industry and the advancement of science and technology, sealing technology plays an increasingly important role in many fields, especially in high-demand environments such as the chemical, aerospace and automotive industries. Fluororubber seals are sealing components made of fluorine rubber as the main raw material, usually used to prevent liquid or gas leakage. Fluororubber contains fluorine in its molecular structure, which gives it excellent chemical and thermal stability, enabling it to exhibit good sealing performance in harsh environments.
[0003] At present, carbon black is the most widely used filler in the fluororubber industry. However, carbon black has the problems of single color, easy to fall off, easy to agglomerate and pollution. Therefore, the development of new fluororubber fillers can help reduce the dependence on carbon black, increase the functionality of fluororubber, and broaden the application field of fluororubber. In addition, fluororubber may be affected by oxidation or external environment during long-term use, which may lead to aging and reduce the reliability of sealing. At the same time, existing flame retardants may affect the physical properties and processing characteristics of fluororubber, thereby reducing its anti-aging ability.
[0004] Therefore, we propose a fluororubber sealing ring based on a sealing pin and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a fluororubber sealing ring based on a sealing pin and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A preparation process of a fluororubber sealing ring based on a sealing pin comprises the following steps:
[0008] Step S1: mixing fluororubber, acid absorbent, plasticizer, reinforcing agent, modified silica and composite filler to obtain a mixed rubber material;
[0009] Step S2: uniformly mixing the mixed rubber material, the vulcanizing agent and the accelerator, sequentially performing first-stage vulcanization and second-stage vulcanization, and then performing a hot pressing molding process to obtain a fluororubber sealing ring.
[0010] Furthermore, the fluororubber sealing ring includes the following components by weight: 80-120 parts of fluororubber, 5-10 parts of acid absorber, 5-15 parts of plasticizer, 10-20 parts of reinforcing agent, 8-16 parts of modified silica, 15-30 parts of composite filler, 5-10 parts of accelerator, and 3-8 parts of vulcanizer.
[0011] Furthermore, the fluororubber is ternary fluororubber.
[0012] Furthermore, the acid absorber is at least one of zinc oxide and magnesium oxide.
[0013] Furthermore, the plasticizer is acetyl tributyl citrate.
[0014] Furthermore, the reinforcing agent is carbon black N990.
[0015] Furthermore, the preparation method of the modified silica is as follows:
[0016] Step A: Evenly mix tea polyphenols and anhydrous ethanol to obtain a tea polyphenol solution; evenly mix 4-vinylbenzeneboric acid and the tea polyphenol solution, adjust the system pH to 9-10 with sodium hydroxide solution, react at 60-70° C. for 10-12 hours, and obtain modified tea polyphenols after reduced pressure distillation and drying;
[0017] Step B: Under nitrogen protection, deionized water, anhydrous ethanol and N,N-dimethylformamide are mixed evenly, modified tea polyphenols and DOPO are added, and azobisisobutyronitrile is added at 70-80°C, reacting for 12-24 hours, and obtaining a flame retardant after reduced pressure distillation and drying;
[0018] Step C: ultrasonically disperse white carbon black in deionized water, add a mixed solution of flame retardant and anhydrous ethanol, stir evenly, add dibutyltin dilaurate, react at 75-85° C. for 10-12 hours, filter, wash and dry to obtain modified white carbon black.
[0019] Furthermore, in step A, the mass ratio of tea polyphenols to anhydrous ethanol is 1:(15-20).
[0020] Furthermore, in step A, the mass ratio of 4-vinylbenzeneboronic acid to tea polyphenols is 1:(3.2-4.0).
[0021] Furthermore, in step B, the mass ratio of deionized water, anhydrous ethanol, N,N-dimethylformamide and modified tea polyphenols is 1:(1-2):1:(0.1-0.2).
[0022] Furthermore, in the step B, the mass ratio of modified tea polyphenols to DOPO is 1:(0.5-0.6).
[0023] Furthermore, in the step B, the amount of azobisisobutyronitrile used is 2-4% of the mass of the modified tea polyphenols.
[0024] Furthermore, in step C, the mass ratio of white carbon black to deionized water is 1:(20-25), the mass ratio of flame retardant to anhydrous ethanol is 1:(15-20), and the mass ratio of white carbon black to flame retardant is 1:(1-2).
[0025] Furthermore, in step C, the amount of dibutyltin dilaurate used is 1-3% of the total mass of white carbon black and the flame retardant.
[0026] In the above technical scheme, tea polyphenol is a polyphenol compound containing a large amount of phenolic hydroxyl groups and having strong antioxidant activity. 4-vinylbenzeneboronic acid and the catechol structure in tea polyphenol can generate borate ester bonds under alkaline conditions to obtain modified tea polyphenol containing vinyl group; the flame retardant is obtained by addition reaction between the PH bond of DOPO and the double bond of the modified tea polyphenol; finally, the abundant silicon hydroxyl groups on the surface of silica and the remaining hydroxyl groups on the surface of the modified tea polyphenol react chemically under the action of a catalyst, and the flame retardant and silica are combined in a chemical bond manner to obtain modified silica with flame retardant and antioxidant effects.
[0027] Furthermore, the preparation method of the composite filler is as follows:
[0028] Step (1): uniformly mixing carbon nanotubes and mixed acid, ultrasonically treating for 5-6 hours, filtering, washing and drying to obtain carboxylated carbon nanotubes;
[0029] Step (2): uniformly mixing carbon fiber, anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, reacting at 55-65° C. for 4-6 hours, filtering, washing and drying to obtain amino carbon fiber; uniformly mixing amino carbon fiber, succinic anhydride and diethanolamine under nitrogen protection, reacting at 115-125° C. for 6-8 hours, adding diethylenetriamine, and reacting at 105-115° C. for 10-12 hours to obtain modified carbon fiber;
[0030] Step (3): mix carboxylated carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole evenly, react for 2-3 hours, add a mixed solution of modified carbon fiber and DMF, add it for 30-50 minutes, react at room temperature for 4-6 hours, filter, wash, Soxhlet extract and dry to obtain a composite filler.
[0031] In the above technical scheme, carbon nanotubes are acidified to prepare carboxylated carbon nanotubes; carbon fibers are modified with 3-aminopropyltrimethoxysilane to obtain amino carbon fibers, which are then reacted with succinic anhydride and diethanolamine to form hyperbranched macromolecules, wherein the hyperbranched polymer has certain toughness, hyperbranched molecules are grafted onto the amino carbon fibers, and secondary amines of diethylenetriamine are reacted with terminal hydroxyl groups of the hyperbranched molecules to introduce amino groups to obtain amino hyperbranched modified carbon fibers, i.e., modified carbon fibers; a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / 1-hydroxybenzotriazole (HOBt) dehydration system is used to promote the condensation reaction between the carboxyl groups in the carboxylated carbon nanotubes and the amino groups in the modified carbon fibers, and the modified carbon fibers are successfully grafted onto the surfaces of the carboxylated carbon nanotubes to obtain composite fillers.
[0032] Furthermore, in step (1), the solid-liquid ratio of carbon nanotubes to mixed acid is 1:(4-6) g / mL.
[0033] Furthermore, in step (1), the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.
[0034] Furthermore, in the step (2), the mass ratio of carbon fiber to anhydrous ethanol, deionized water, and 3-aminopropyltrimethoxysilane is 1:(4-6):(1-2):(0.5-0.8).
[0035] Furthermore, in the step (2), the mass ratio of the amino carbon fiber, succinic anhydride, diethanolamine and diethylenetriamine is 1:(1.5-2.5):(2-3):(3-4).
[0036] Furthermore, in the step (3), the mass ratio of carboxylated carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is 1:(0.1-0.2):(0.08-0.10).
[0037] Furthermore, in the step (3), the mass ratio of the carboxylated carbon nanotubes, the modified carbon fibers and DMF is 1:(2-4):(5-10).
[0038] Furthermore, the accelerator is triallyl isocyanurate.
[0039] Furthermore, the vulcanizing agent is a dipentadienyl vulcanizing agent.
[0040] Furthermore, the mixing process conditions are: mixing temperature 90-110° C., mixing time 2-10 min.
[0041] Furthermore, the process conditions of the one-stage vulcanization are: carried out on a flat vulcanizing machine, the vulcanization temperature is 160-170° C., the pressure is 14-16 MPa, and the time is 8-12 min.
[0042] Furthermore, the process conditions of the two-stage vulcanization are: carried out in a constant temperature box, the vulcanization temperature is 200-250° C., and the time is 14-24 hours.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. A fluororubber sealing ring based on a sealing pin and a preparation process thereof of the present invention comprises the following steps: 4-vinylbenzeneboric acid and the catechol structure in tea polyphenols can generate a borate ester bond under alkaline conditions to obtain a modified tea polyphenols containing vinyl groups; a flame retardant is obtained by an addition reaction between the PH bond of DOPO and the double bond of the modified tea polyphenols; finally, the abundant silicon hydroxyl groups on the surface of silica react with the remaining hydroxyl groups on the surface of the modified tea polyphenols under the action of a catalyst to achieve a chemical reaction between the flame retardant and silica in a chemically bonded manner to obtain a modified silica with flame retardant and antioxidant effects, which can effectively reduce the flammability of fluororubber under high temperature conditions, thereby improving its safety and application reliability, and also significantly improve the aging resistance of the fluororubber sealing ring, thereby improving its performance stability and sealing effect in long-term use.
[0045] 2. The fluororubber sealing ring based on the sealing pin and the preparation process thereof of the present invention adopt a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) / 1-hydroxybenzotriazole (HOBt) dehydration system to promote the condensation reaction between the carboxyl groups in the carboxylated carbon nanotubes and the amino groups in the modified carbon fibers, and successfully graft the modified carbon fibers onto the surface of the carboxylated carbon nanotubes to prepare a composite filler, which not only improves the tensile strength and wear resistance of the material and prolongs its service life, but also exhibits excellent thermal stability in a high temperature environment, ensuring that it can still maintain excellent performance under harsh working conditions. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In this embodiment, fluororubber: ternary fluororubber, brand FE2463; acid absorber: magnesium oxide, model MA-150; reinforcing agent: carbon black N990, model CORAX N990; vulcanizing agent: dipentadienyl vulcanizing agent, model TC-101; white carbon black: precipitated white carbon black, model TH-5020, sourced from Shandong Wanhua Tianhe New Materials Co., Ltd.; carbon nanotube: model NACODC8, sourced from Jiaxing Naco New Materials Co., Ltd.; carbon fiber: T700 chopped carbon fiber, 3 mm long, sourced from Shanghai Lishuo Composite Materials Technology Co., Ltd.
[0048] In the following examples and comparative examples, 1 part is equal to 10 g.
[0049] Embodiment 1: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0050] Step S1: mixing 80 parts of fluororubber, 5 parts of acid absorber, 5 parts of plasticizer, 10 parts of reinforcing agent, 8 parts of modified silica and 15 parts of composite filler at 90° C. for 2 minutes to obtain a mixed rubber material;
[0051] Step S2: the mixed rubber material is uniformly mixed with 3 parts of a vulcanizing agent and 5 parts of an accelerator, and first-stage vulcanization (carried out on a flat vulcanizing machine, the vulcanization temperature is 160° C., the pressure is 14 MPa, and the time is 8 min) and second-stage vulcanization (carried out in a constant temperature box, the vulcanization temperature is 200° C., and the time is 14 h) are successively performed, and then a hot pressing molding process is performed to obtain a fluororubber sealing ring;
[0052] The preparation method of modified silica is as follows:
[0053] Step A: 8 parts of tea polyphenols and 120 parts of anhydrous ethanol are mixed evenly to obtain a tea polyphenol solution; 2.5 parts of 4-vinylbenzeneboric acid and the tea polyphenol solution are mixed evenly, and the pH value of the system is adjusted to 9 with a sodium hydroxide solution, and the reaction is carried out at 60° C. for 10 hours, and after vacuum distillation and drying, a modified tea polyphenol is obtained;
[0054] Step B: Under nitrogen protection, 80 parts of deionized water, 80 parts of anhydrous ethanol and 80 parts of N,N-dimethylformamide were mixed evenly, 8 parts of modified tea polyphenols and 4 parts of DOPO were added, and 0.16 parts of azobisisobutyronitrile were added at 70°C, reacted for 12 hours, and after reduced pressure distillation and drying, a flame retardant was obtained;
[0055] Step C: ultrasonically dispersing 8 parts of white carbon black in 160 parts of deionized water, adding a mixed solution of 8 parts of flame retardant and 120 parts of anhydrous ethanol, stirring evenly, adding 0.16 parts of dibutyltin dilaurate, reacting at 75° C. for 10 hours, filtering, washing and drying to obtain modified white carbon black;
[0056] The preparation method of the composite filler is as follows:
[0057] Step (1): 5 parts of carbon nanotubes and 200 mL of mixed acid (prepared with concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) were mixed evenly, ultrasonically treated for 5 hours, filtered, washed, and dried to obtain carboxylated carbon nanotubes;
[0058] Step (2): 10 parts of carbon fiber, 40 parts of anhydrous ethanol, 10 parts of deionized water, and 5 parts of 3-aminopropyltrimethoxysilane are mixed evenly, reacted at 55°C for 4 hours, filtered, washed, and dried to obtain amino carbon fiber; under nitrogen protection, 10 parts of amino carbon fiber, 15 parts of succinic anhydride, and 20 parts of diethanolamine are mixed evenly, reacted at 115°C for 6 hours, and then 30 parts of diethylenetriamine are added, and reacted at 105°C for 10 hours to obtain modified carbon fiber;
[0059] Step (3): Mix 5 parts of carboxylated carbon nanotubes, 0.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.4 parts of 1-hydroxybenzotriazole evenly, react for 2 hours, add a mixed solution of 10 parts of modified carbon fibers and 50 parts of DMF dropwise, and add the mixture for 30 minutes. React at room temperature for 4 hours, filter, wash, Soxhlet extract and dry to obtain a composite filler.
[0060] Embodiment 2: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0061] Step S1: mixing 100 parts of fluororubber, 8 parts of acid absorber, 10 parts of plasticizer, 15 parts of reinforcing agent, 12 parts of modified silica and 20 parts of composite filler at 100° C. for 5 minutes to obtain a mixed rubber material;
[0062] Step S2: the mixed rubber material, 5 parts of vulcanizing agent and 8 parts of accelerator are uniformly mixed, and first-stage vulcanization (carried out on a flat vulcanizing machine, the vulcanization temperature is 165°C, the pressure is 15MPa, and the time is 10min) and second-stage vulcanization (carried out in a constant temperature box, the vulcanization temperature is 220°C, and the time is 20h) are sequentially performed, and then a hot pressing molding process is performed to obtain a fluororubber sealing ring;
[0063] The preparation method of modified silica is as follows:
[0064] Step A: 18 parts of tea polyphenols and 320 parts of anhydrous ethanol are mixed evenly to obtain a tea polyphenol solution; 5 parts of 4-vinylbenzeneboric acid and the tea polyphenol solution are mixed evenly, and the pH value of the system is adjusted to 9.5 with a sodium hydroxide solution, and the reaction is carried out at 65° C. for 11 hours, and after vacuum distillation and drying, a modified tea polyphenol is obtained;
[0065] Step B: Under nitrogen protection, 120 parts of deionized water, 180 parts of anhydrous ethanol and 120 parts of N,N-dimethylformamide were mixed evenly, 18 parts of modified tea polyphenols and 10 parts of DOPO were added, and 0.54 parts of azobisisobutyronitrile were added at 75°C, reacted for 18 hours, and after reduced pressure distillation and drying, a flame retardant was obtained;
[0066] Step C: ultrasonically dispersing 12 parts of white carbon black in 270 parts of deionized water, adding a mixed solution of 18 parts of flame retardant and 320 parts of anhydrous ethanol, stirring evenly, adding 0.6 parts of dibutyltin dilaurate, reacting at 80° C. for 11 hours, filtering, washing and drying to obtain modified white carbon black;
[0067] The preparation method of the composite filler is as follows:
[0068] Step (1): 5 parts of carbon nanotubes and 28 mL of mixed acid (prepared with concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) were mixed evenly, and ultrasonic treatment was performed for 5.5 hours. After filtering, washing, and drying, carboxylated carbon nanotubes were obtained;
[0069] Step (2): 15 parts of carbon fiber, 75 parts of anhydrous ethanol, 22 parts of deionized water, and 9 parts of 3-aminopropyltrimethoxysilane are mixed evenly, reacted at 60°C for 5 hours, filtered, washed, and dried to obtain amino carbon fiber; under nitrogen protection, 15 parts of amino carbon fiber, 30 parts of succinic anhydride, and 38 parts of diethanolamine are mixed evenly, reacted at 120°C for 7 hours, and then 52 parts of diethylenetriamine are added, and reacted at 110°C for 11 hours to obtain modified carbon fiber;
[0070] Step (3): Mix 5 parts of carboxylated carbon nanotubes, 0.75 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.45 parts of 1-hydroxybenzotriazole evenly, react for 2.5 hours, add a mixed solution of 15 parts of modified carbon fibers and 100 parts of DMF dropwise, and add the mixture for 40 minutes. React at room temperature for 5 hours, filter, wash, Soxhlet extract and dry to obtain a composite filler.
[0071] Embodiment 3: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0072] Step S1: mixing 120 parts of fluororubber, 10 parts of acid absorber, 15 parts of plasticizer, 20 parts of reinforcing agent, 16 parts of modified silica and 30 parts of composite filler at 110° C. for 10 minutes to obtain a mixed rubber material;
[0073] Step S2: the mixed rubber material, 8 parts of vulcanizing agent and 10 parts of accelerator are uniformly mixed, and first-stage vulcanization (carried out on a flat vulcanizer, the vulcanization temperature is 170°C, the pressure is 16MPa, and the time is 12min) and second-stage vulcanization (carried out in a constant temperature box, the vulcanization temperature is 250°C, and the time is 24h) are sequentially performed, and then a hot pressing molding process is performed to obtain a fluororubber sealing ring;
[0074] The preparation method of modified silica is as follows:
[0075] Step A: 32 parts of tea polyphenols and 640 parts of anhydrous ethanol are mixed evenly to obtain a tea polyphenol solution; 8 parts of 4-vinylbenzeneboric acid and the tea polyphenol solution are mixed evenly, and the pH value of the system is adjusted to 10 with a sodium hydroxide solution, and the reaction is carried out at 70° C. for 12 hours, and after vacuum distillation and drying, a modified tea polyphenol is obtained;
[0076] Step B: Under nitrogen protection, 160 parts of deionized water, 320 parts of anhydrous ethanol and 160 parts of N,N-dimethylformamide were mixed evenly, 32 parts of modified tea polyphenols and 19.2 parts of DOPO were added, and 1.28 parts of azobisisobutyronitrile were added at 80°C, reacted for 24 hours, and after reduced pressure distillation and drying, a flame retardant was obtained;
[0077] Step C: ultrasonically dispersing 16 parts of white carbon black in 400 parts of deionized water, adding a mixed solution of 32 parts of a flame retardant and 640 parts of anhydrous ethanol, stirring evenly, adding 1.44 parts of dibutyltin dilaurate, reacting at 85° C. for 12 hours, filtering, washing, and drying to obtain modified white carbon black;
[0078] The preparation method of the composite filler is as follows:
[0079] Step (1): 6 parts of carbon nanotubes and 36 parts of mixed acid (prepared by concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) are mixed evenly, ultrasonically treated for 6 hours, filtered, washed, and dried to obtain carboxylated carbon nanotubes;
[0080] Step (2): 24 parts of carbon fiber, 144 parts of anhydrous ethanol, 48 parts of deionized water, and 19.2 parts of 3-aminopropyltrimethoxysilane are mixed evenly, reacted at 65°C for 6 hours, filtered, washed, and dried to obtain amino carbon fiber; under nitrogen protection, 24 parts of amino carbon fiber, 60 parts of succinic anhydride, and 72 parts of diethanolamine are mixed evenly, reacted at 125°C for 8 hours, and then 96 parts of diethylenetriamine are added, and reacted at 115°C for 12 hours to obtain modified carbon fiber;
[0081] Step (3): 6 parts of carboxylated carbon nanotubes, 1.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.6 parts of 1-hydroxybenzotriazole are mixed evenly, and the mixture is reacted for 3 hours. A mixed solution of 24 parts of modified carbon fibers and 60 parts of DMF is added dropwise for 50 minutes, and the mixture is reacted at room temperature for 6 hours. After filtering, washing, Soxhlet extraction and drying, a composite filler is obtained.
[0082] Comparative Example 1: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0083] Compared with Example 2, in Comparative Example 1, the modified silica in step S1 is replaced with silica of the same mass, and the other steps are the same as those in Example 2.
[0084] Comparative Example 2: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0085] Compared with Example 2, the composite filler in Comparative Example 2 consists of 5 parts of carbon nanotubes and 15 parts of carbon fibers, and the other steps are the same as those in Example 2.
[0086] Comparative Example 3: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0087] Compared with Example 2, in Comparative Example 3, the modified carbon fiber in step (3) is replaced with carbon fiber of the same mass, and the other steps are the same as those in Example 2.
[0088] Comparative Example 4: A preparation process of a fluororubber sealing ring based on a sealing pin, comprising the following processes:
[0089] Compared with Example 2, in step (3) of Comparative Example 4, the mass ratio of carboxylated carbon nanotubes to modified carbon fibers is 1:1, and the other steps are the same as those of Example 2.
[0090] Experiment: Take the fluororubber sealing rings obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results:
[0091] The tensile strength was measured according to GB / T 528-2009 standard, with a tensile rate of 500 mm / min. The aging resistance was measured according to ISO 188 standard, with the sample placed in a vacuum oven at 180°C for an aging test. After aging for 144 hours, the tensile strength before and after aging was measured, and the tensile strength retention rate was calculated. According to the UL94 flame retardant grade test, the generation of molten droplets was observed. If no molten droplets appeared, it indicated that the flame retardant performance was good; otherwise, it showed poor flame retardant performance.
[0092] Test Results
[0093] Tensile strength MPa Tensile strength retention rate % Flame retardant Example 1 14.8 62.6 good Example 2 15.7 64.8 good Example 3 15.5 63.5 good Comparative Example 1 12.1 50.3 Difference Comparative Example 2 10.6 59.7 good Comparative Example 3 11.3 60.6 good Comparative Example 4 13.2 61.9 good
[0094] According to the data in the above table, we can clearly draw the following conclusions:
[0095] 1. Compared with Examples 1-3, the aging resistance and flame retardancy of the product obtained in Comparative Example 1 decreased, which shows that the modified silica prepared by the present invention can effectively improve the aging resistance and flame retardancy of the material.
[0096] 2. Compared with Examples 1-3, the tensile strength of the products obtained in Comparative Examples 2 and 3 decreases, indicating that the composite filler prepared by the present invention can significantly improve the tensile properties of the material; at the same time, compared with the unmodified carbon fiber, the modified carbon fiber prepared by the present invention can be effectively combined with the carboxylated carbon nanotubes, further improving the mechanical properties of the material.
[0097] 3. Compared with Examples 1-3, the tensile strength of the product obtained in Comparative Example 4 is reduced. It can be seen that the composite filler prepared by the present invention is affected by its component ratio. By selecting the component ratio within the range, a material with excellent tensile properties can be prepared.
[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0099] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of a fluororubber sealing ring based on a sealing pin, characterized in that: The steps include: Step S1: mixing fluororubber, acid absorbent, plasticizer, reinforcing agent, modified silica and composite filler to obtain a mixed rubber material; Step S2: uniformly mixing the mixed rubber material, the vulcanizing agent and the accelerator, sequentially performing first-stage vulcanization and second-stage vulcanization, and then performing a hot pressing molding process to obtain a fluororubber sealing ring.
2. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 1, characterized in that: The fluororubber sealing ring comprises the following components by weight: 80-120 parts of fluororubber, 5-10 parts of acid absorber, 5-15 parts of plasticizer, 10-20 parts of reinforcing agent, 8-16 parts of modified white carbon black, 15-30 parts of composite filler, 5-10 parts of accelerator and 3-8 parts of vulcanizer.
3. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The fluororubber is a ternary fluororubber.
4. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The acid scavenger is at least one of zinc oxide and magnesium oxide.
5. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The plasticizer is acetyl tributyl citrate.
6. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The reinforcing agent is carbon black N990.
7. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The preparation method of the modified white carbon black is as follows: Step A: Evenly mix tea polyphenols and anhydrous ethanol to obtain a tea polyphenol solution; evenly mix 4-vinylbenzeneboric acid and the tea polyphenol solution, adjust the system pH to 9-10 with sodium hydroxide solution, react at 60-70° C. for 10-12 hours, and obtain modified tea polyphenols after reduced pressure distillation and drying; Step B: Under nitrogen protection, deionized water, anhydrous ethanol and N,N-dimethylformamide are mixed evenly, modified tea polyphenols and DOPO are added, and azobisisobutyronitrile is added at 70-80°C, reacting for 12-24 hours, and obtaining a flame retardant after reduced pressure distillation and drying; Step C: ultrasonically disperse white carbon black in deionized water, add a mixed solution of flame retardant and anhydrous ethanol, stir evenly, add dibutyltin dilaurate, react at 75-85° C. for 10-12 hours, filter, wash and dry to obtain modified white carbon black.
8. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The preparation method of the composite filler is as follows: Step (1): uniformly mixing carbon nanotubes and mixed acid, ultrasonically treating for 5-6 hours, filtering, washing and drying to obtain carboxylated carbon nanotubes; Step (2): uniformly mixing carbon fiber, anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, reacting at 55-65° C. for 4-6 hours, filtering, washing and drying to obtain amino carbon fiber; uniformly mixing amino carbon fiber, succinic anhydride and diethanolamine under nitrogen protection, reacting at 115-125° C. for 6-8 hours, adding diethylenetriamine, and reacting at 105-115° C. for 10-12 hours to obtain modified carbon fiber; Step (3): mix carboxylated carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole evenly, react for 2-3 hours, add a mixed solution of modified carbon fiber and DMF, add it for 30-50 minutes, react at room temperature for 4-6 hours, filter, wash, Soxhlet extract and dry to obtain a composite filler.
9. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The mixing process conditions are: mixing temperature 90-110° C., mixing time 2-10 min.
10. The process for preparing a fluororubber sealing ring based on a sealing pin according to claim 2, characterized in that: The process conditions of the one-stage vulcanization are: carried out on a flat vulcanizing machine, the vulcanization temperature is 160-170° C., the pressure is 14-16 MPa, and the time is 8-12 minutes.